Analysis of the cultural productivity of crop rotation systems for wheat, under no-tillage - Santos, Henrique Pereira dos; Ignaczak, João Carlos; Wobeto, Celso (Pesquisa Agropecuaria Brasileira, 1996)
From 1984 to 1993, in Guarapuava, PR, Brazil, the effect of systems of crop rotation on wheat was assessed. Four rotation systems for wheat were studied: system I (wheat/soybean); system II (wheat/soybean, common vetch/corn, from 1984 to 1989, and wheat/soybean, white oats/soybean, from 1990 to 1993); system III (wheat/soybean, flax/soybean, and common vetch/corn, from 1984 to 1989, and wheat/soybean, common vetch/corn, and white oats/soybean, from 1990 to 1993); and system IV (wheat/soybean, legume/corn, barley/soybean, and white oats/soybean). Cultural productivity (kg of commodity/Mcal consumed) during that period is presentend in this paper. From 1984 to 1989, systems II (2.20 kg/Mcal), III (1.91 kg/Mcal), and IV (1.83 kg/Mcal) showed a higher conversion rate, as compared to system I (1.52 kg/Mcal); system II was the best option. From 1990 to 1993 systems II, III, and IV, whose average cultural productivity indexes were 1.93 kg/Mcal, 1.96 kg/Mcal, and 1.91 kg/Mcal, respectively, did not differ from system I (1.78 kg/Mcal); however, the annual cultural productivity indexes of system II showed no difference from system II or exceeded it, becoming, therefore, a good alternative to replace wheat/soybean monoculture.